Migration Characteristics of Boring Mud in Roadway Floor Anchor Wire Hole and Test in Coal Mine - Hui Zhang; Weihai Han; Youlin Xu; Mengzhi Zhu; Zhanyang Liu; Zhenfeng Wang (Advances in Civil Engineering)
Given the difficulty in drilling the anchor holes in the roadway floor of the coal mine, the characteristics of slag movement in the process of positive and negative circulation drilling are analyzed. It is concluded that the interaction between the three zones of drilling and slag is the fundamental reason restricting the rapid drilling of the anchor cable hole in the floor, and it is proposed that the pump reverse circulation drilling can effectively prevent the formation of the three zones of drilling and slag. According to the actual situation, the relationship between drilling depth, vacuum degree of the pump, and the velocity of drilling fluid and the volume of drilling slag is obtained. The results show that the pump suction reverse circulation is feasible for the rapid drilling of the anchor hole of the floor. A set of pump suction reverse circulation drilling systems has been developed, and floor anchor wire hole drilling and slag discharge operation at the same time were realized. The field test shows that the effective drilling time of the anchor cable hole in the depth of 5.6 m can be controlled within 30 min, which solves the problem of deep hole drilling in the anchor hole of the bottom plate and purifies the working environment.